Cloud computing for brain segmentation – a perspective from the technology and evaluations. (25th January 2015) - Chang, Victor
This paper examines how cloud computing can be used in the area of brain segmentation with regard to satisfactory technical and user evaluations. It explains eleven APIs associated with each brain segment and the process of capturing data for each segment. Functionality and experiments associated with each API are discussed. Dancing is to capture data more easily. Results are used to explain why some segments are more active in dancing, with two evaluations undertaken. The first evaluation is the use of brain segmentations developed for medical cloud computing education (MCCE) and results confirm that cloud computing offers a 20% improvement in learning satisfaction. The second evaluation is focused on recapturing a lost skill. Results confirm that volunteers have their heartbeat, blood pressure, emotion, body coordination and vision at their peak. Benefits of using cloud brain segmentation technology are presented to illustrate positive impacts to healthcare informatics, education and cost reduction.